Effect of Different Approaches to Intravenous Nutrition on the Pattern of Weight Gain in Very Low Birth Weight Preterm Neonates: A Randomized Clinical Trial - Ali Maleky; Majid Hamidi; Afsaneh Malekpour Tehrani; Roya Choupani Dastgerdi; Marzieh Khalili; Mohammad Mehdi Mirforoughi (Mashhad University of Medical Sciences, 2023)
Background: Low birth weight neonates have low energy reserves; thus, postpartum feeding is required to meet their ongoing nutritional requirements. Total parenteral nutrition (TPN) provides critical nutrients for the metabolism and development of neonates; however, few studies have investigated the effect of TPN on the early growth patterns of neonates. The present study examined the effects of TPN on preterm neonate anthropometric characteristics using two commonly used TPN calorie introduction techniques. Methods: This randomized clinical trial studied preterm neonates with birth weights of less than 1500 g. Calories were initiated at a rate of 3 g/kg for lipids and 3.5 g/kg for amino acids in the intervention group. In the control group, the amino acid solution was begun at 1 g/kg/day and the lipid solution at 0.5 g/kg/day, and both were increased daily by 1 g/kg to a maximum of 3.5 and 3 g/kg/day for amino acids and lipids, respectively. In this group, all neonates reached full calorie intake at 3 to 5 days of age. The trend of change in the anthropometric parameters was evaluated and compared. Results: Although both groups showed an increase in neonatal weight, length and head circumference, no statistically significant difference was observed between them. Both groups had similar lengths of hospital stay. Conclusion: Based on the findings of the present study, TPN feeding done using two approaches to amino acid and lipid administration had no significant influence on hospital stay, TPN duration, or growth indices in preterm neonates weighing less than 1500 g.